Makna Judul The Good Bad Mother: Sebuah Kajian Semiotika Roland Barthes - Azhari, Diazti Salsabila; Fadillah, Dani (Universitas Muhammdiyah Yogyakarta, 2025)
The title of an audiovisual work serves not only as an identity but also as an initial representation of the theme, conflict, and message being conveyed. This study aims to analyze the meaning of the title